Teaching work routine: challenges to nursing professors in contemporary times - D’Oliveira, Camila Arantes Ferreira Brecht; Souza, Norma Valéria Dantas de Oliveira; Varella, Thereza Christina Mó Y Mó Loureiro; Vargens, Octávio Muniz da Costa; Noronha, Isabela da Rosa (Revista da Escola de Enfermagem da USP, 2020)
Objective: To describe the organization of nursing professors’ work and analyze its limiting and facilitating aspects. Method: A qualitative and descriptive study composed of professors from the federal public universities of Rio de Janeiro. Data collection took place through semi-structured interviews. The content analysis technique was used for data processing. Results: Twenty-seven (27) professors participated. Facilitating elements of the teaching work were: work environment; autonomy and flexibility; liking what they do; use of technologies; and solidarity of the professional group; while hindering elements included: high work demand; intense work rhythm; scarcity of material and human resources; and academic competitiveness. Conclusion: The configuration of the teaching work organization is complex and multifaceted, presenting high psycho-affective, cognitive and physical demands which enhance illness in these workers.